2018
DOI: 10.1111/jmwh.12728
|View full text |Cite
|
Sign up to set email alerts
|

Variables That Influence US Midwife and Physician Management of the Third Stage of Labor

Abstract: This study identifies variables reported as influencing clinical decision making during the third stage of labor. Therefore, these variables are important to consider when evaluating interventions and outcomes related to management of the third stage of labor and any attempts to design new interventions. The findings are descriptive of practice; they are not intended to guide changes in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A national survey of nurse-midwives, certified professional midwives, family practice physicians, and obstetricians found that routine care during the third stage of labor included more than 100 identified practices. 25,26 These practice differences spanned environmental, maternal, medical or pharmacologic, and other components of care. In addition, it is unclear what effect lighting, noise (including phone or pagers), number of people present, or other birthing environmental variables have on physiologic completion of the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A national survey of nurse-midwives, certified professional midwives, family practice physicians, and obstetricians found that routine care during the third stage of labor included more than 100 identified practices. 25,26 These practice differences spanned environmental, maternal, medical or pharmacologic, and other components of care. In addition, it is unclear what effect lighting, noise (including phone or pagers), number of people present, or other birthing environmental variables have on physiologic completion of the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…The wide variation of practices midwives and physicians provide during the normal third stage of labor creates significant challenges for researchers and clinicians. A national survey of nurse‐midwives, certified professional midwives, family practice physicians, and obstetricians found that routine care during the third stage of labor included more than 100 identified practices 25,26 . These practice differences spanned environmental, maternal, medical or pharmacologic, and other components of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these recommendations, some professionals opt for expectant management based on the fact that this method contributes to a more natural childbirth experience, the belief that active management is unnecessary in low-risk women, and the desire to avoid the effects associated with the use of the most habitual uterotonics [26]. In 2018, Schorn et al identified that active bleeding, current recommendations or guidelines, and maternal or family preferences are the variables that influence clinical decisions on how to manage this stage [27].…”
Section: Discussionmentioning
confidence: 99%
“…Increased awareness of rising PPH‐related morbidity has led to state and national initiatives for PPH risk assessment, prevention, and treatment using bundles of care 9 . However, little is known about how practitioners attending women in the community setting in the United States approach third‐stage labor management, use of preventive strategies for PPH, treatment, and rates of hospital transfer for prolonged third‐stage labor and/or PPH 10 . In addition, the methods midwives use for third‐stage management may be influenced by training, form of licensure, certification, and/or state‐level regulations that either prohibit or support their practice, and access to and use of uterotonic medications.…”
Section: Introductionmentioning
confidence: 99%